The Relationship Between Knowledge and Education Level and IUD Choice Among Fertile-Age Couples in the Muara Kelingi Community Health Center Work Area Musirawas Regency 2025 - Ema Martini; Liya Lugita Sari; Bella Anarkie (Student Scientific Journal, 2026)
According to WHO data from 2022, of the 1.9 billion women of childbearing age (15–49 years old) worldwide in 2021, 1.1 billion needed family planning. In Indonesia, in 2024, the majority of acceptors chose injectables (35.39%), followed by pills (7.54%), and IUDs (6.08%). The purpose of this study was to determine the relationship between knowledge and education level and IUD choice among couples of childbearing age at the Muara Kelingi Community Health Center in Musi Rawas Regency in 2025. The study used a cross-sectional design, with data collected by distributing questionnaires. The population in this study was 5,501 couples of childbearing age, with a sample of 95 respondents using a simple random sampling technique. The study was conducted in the Muara Kelingi Community Health Center (Puskesmas) working area in Musi Rawas Regency from December 23, 2025, to January 6, 2026. Univariate analysis results indicated that almost half of the respondents (36.8%) of fertile couples in the Muara Kelingi Community Health Center working area in Musi Rawas Regency in 2025 had insufficient knowledge. The majority of respondents (57.9%) had low education levels, and the majority (72.6%) of respondents did not use an IUD. Bivariate analysis results showed a significant relationship between knowledge and IUD choice (p-value 0.012). There was also a significant relationship between education level and IUD choice (p-value 0.034). It is hoped that fertile couples will be more active in participating in family planning counseling, community health centers will improve the quality of counseling and involve their husbands, educational institutions will strengthen family planning counseling education, and future researchers will examine other factors influencing IUD choice.